Outcomes of autologous bone marrow mononuclear cell administration combined with educational intervention in the treatment of autism spectrum disorder: a randomized, open-label, controlled phase II clinical trial - Liem Thanh Nguyen; Phuong Mai Nguyen; Hoang-Phuong Nguyen; Hau Thi Bui; Lan Thi Mai Dao; Minh Van Pham; Chi Khanh Hoang; Phuong Thi Nguyen; Thao Thi Phuong Nguyen; Anh Thi Phuong Nguyen; Van Thi Hoang; Hoa Thi Phuong Bui; et al. (Stem Cell Research & Therapy)
Abstract Background This study evaluated the effectiveness of intrathecal autologous bone marrow mononuclear cell (BMMNC) therapy combined with education compared with education alone for the treatment of autism spectrum disorder (ASD). Methods Fifty-four children with ASD, aged three to seven years, were randomly assigned to two groups. Fifty patients completed the study (25 patients per group). The cell therapy (CT) group received two BMMNC infusions six months apart along with an educational intervention, while the control group received education only. Efficacy outcomes were assessed at baseline, two, six, and 12 months, based on: (1) changes in ASD severity evaluated through the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), the Childhood Autism Rating Scale (CARS), and the Clinical Global Impression-Severity (CGI-S) scale scores and (2) improvements in social interaction, adaptive behavior, and daily living skills measured by the Vineland Adaptive Behavior Scales (VABS-II) and Clinical Global Impression-Improvement (CGI-I) scale scores. Results At 12 months, the CT group presented a 48.0% reduction in individuals classified at the most severe DSM-5 level compared with 8.0% in the control group (p = 0.004). The CARS scores were significantly lower in the CT group (-5.9 points) than in the control group (-1.5 points) (p < 0.0001). Similarly, the CT group exhibited greater improvement in CGI-S scores (-1.5 points) than did the control group (-0.1 points) (p < 0.0001). The VABS-II scores increased by 8.5 points in the CT group versus 1.4 points in the control group (p < 0.0001). Finally, the CGI-I scores improved from 2.8 to 2.0 in the CT group but worsened from 3.0 to 3.5 in the control group (p < 0.0001). Conclusions Intrathecal BMMNC combined with an educational intervention improved disease severity and adaptability more than education alone in children with ASD. Trial registration clinicaltrials.gov, NCT05307536. Date registered 12 February 2022. http://clinicaltrials.gov/study/NCT05307536 .